2022
DOI: 10.3389/fimmu.2022.877533
|View full text |Cite
|
Sign up to set email alerts
|

Distal Consequences of Mucosal Infections in Intestinal and Lung Inflammation

Abstract: Infectious diseases are one of the leading causes of morbidity and mortality worldwide, affecting high-risk populations such as children and the elderly. Pathogens usually activate local immune responses at the site of infection, resulting in both protective and inflammatory responses, which may lead to local changes in the microbiota, metabolites, and the cytokine environment. Although some pathogens can disseminate and cause systemic disease, increasing evidence suggests that local infections can affect tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 122 publications
(165 reference statements)
0
11
0
Order By: Relevance
“…Based on multiple signals derived from the microbiota, gut and lung may have bidirectional interactions. However, the outcomes are still incompletely understood [ 69 ]. Exploring these possibilities is an exciting and vital task for future research.…”
Section: Mechanisms Regulating Glamentioning
confidence: 99%
“…Based on multiple signals derived from the microbiota, gut and lung may have bidirectional interactions. However, the outcomes are still incompletely understood [ 69 ]. Exploring these possibilities is an exciting and vital task for future research.…”
Section: Mechanisms Regulating Glamentioning
confidence: 99%
“…Accordingly, research on helminth therapy provides another clue to the benefits of gut microbiota balance on the respiratory system, and it is also expected to become another clue for the prevention and treatment of asthma. Researchers have discovered that helminths affect the composition of gut microbiota and indirectly affect the lung immune response and prevent asthma attacks 142 . Studies have shown that mice infected with Heligmosomoides polygyrus bakeri will change the composition of gut microbiota by increasing SCFAs and ultimately resulting in reduced inflammation in dust mites‐induced asthma models 143 …”
Section: Manipulate the Gut Microbiota To Fight Asthmamentioning
confidence: 99%
“…Researchers have discovered that helminths affect the composition of gut microbiota and indirectly affect the lung immune response and prevent asthma attacks. 142 Studies have shown that mice infected with Heligmosomoides polygyrus bakeri will change the composition of gut microbiota by increasing SCFAs and ultimately resulting in reduced inflammation in dust mites‐induced asthma models. 143 …”
Section: Manipulate the Gut Microbiota To Fight Asthmamentioning
confidence: 99%
“…Several harmful bacteria were found to be responsible for IBD pathogenesis, such as Firmicutes (abundant in bare sand), Proteobacteria , and Roseburia spp., including Roseburia faecis and Roseburia intestinalis [ 19 ]. The relative increase of these species in the gut, leads to their attachment to colonic mucosa, thus affecting and increasing its permeability [ 20 ]. As for CRC, the exact pathogenesis is unclear and needs further investigation [ 21 ].…”
Section: Introductionmentioning
confidence: 99%